IMPLEMENTASI MEDIA KINEMASTER BERBASIS IPTEK PADA PEMBELAJARAN AKSARA KAGANGA DI SEKOLAH DASAR SEBAGAI LOCAL WISDOM BENGKULU UTARA - supriatna, irfan; Herman; Salati Asmahasanah (UNIB Press, 2024)
This research is motivated by the lack of creativity of a teacher in utilizing existing media, especially based on science and technology, so that students have difficulty understanding the kaganga script in elementary schools. One example of an area that developed the Kaganga script and became part of learning in schools is the Rejang Tribe in North Bengkulu. The Kaganga script as local wisdom in Bengkulu, especially in North Bengkulu, is expected to be able to preserve local languages ​​in teaching and civilizing local languages ​​well so as to prevent extinction in the present and in the future. Most of the learning media used are still conventional, namely textbook-based and have not used science and technology-based media. Currently, Indonesia is having a difficult time due to the COVID-19 pandemic, so learning in schools uses online learning. Therefore, the implementation of kinemaster media is an alternative solution in the midst of the covid-19 pandemic. The purpose of this study was to determine the effectiveness of the implementation of kinemaster media based on science and technology in learning the Kaganga script in elementary schools as local wisdom of North Bengkulu. The research method used is descriptive qualitative with several stages, namely identifying significant problems, formulating problems clearly, determining the objectives and benefits of research, conducting literature studies related to the problem, determining the framework of thinking, research questions, and research hypotheses, designing research methods, determine population, sample, sampling technique, determine data collection instrument, and data analysis, make research report.